Creating opportunities for young coffee farmers in Honduras using climate services - Giraldo Mendez, Diana Carolina; Jiménez, Gabriela; Obando, Diego; Clarkson, Graham; Dorward, Peter (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Young leaders in their communities successfully acted as facilitators of PICSA implementation in a scalable process, working in a network with the relevant coffee stakeholders in a collaborative learning process. Young people can act as generators of change in their communities through digital inclusion which enables them to share local information to support coffee farmers’ decision-making. The online PICSA training of young people in rural communities has considerable potential but requires additional facilitator skills and new approaches. It can also complement face-to-face activities and training. IHCAFE is interested in using PICSA as a climate service and as a system to support their coffee extension services.